2014
DOI: 10.1590/s0103-84782014000400020
|View full text |Cite
|
Sign up to set email alerts
|

Farelo de crambe nas formas in natura ou reduzida em antinutrientes na dieta do jundiá

Abstract: Farelo de crambe nas formas in natura ou reduzida em antinutrientes na dieta do jundiá.Ciência Rural, v.44, n.4, abr, 2014.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
4
0
3
Order By: Relevance
“…A utilização de farelo de crambe na alimentação animal vem sendo estudada principalmente para ruminantes como bovinos de corte (Mendonça et al, 2015), bovinos de leite (Oliveira et al, 2016) e ovinos (Goes et al, 2010;Dorigon e Gai (2016), entretanto, são escassos os estudos para os não ruminantes, havendo alguns trabalhos com juvenis de jundiá (Lovatto et al, 2014;Pettro et al, 2014), tilápias do Nilo (Moura et al, 2015) e frangos de corte (Ledoux et al, 1999). Portanto, objetivou-se com o presente trabalho determinar o desempenho de frangos de corte na fase inicial de vida, alimentados com farelo de crambe como fonte proteica para a ração.…”
Section: Resultsunclassified
“…A utilização de farelo de crambe na alimentação animal vem sendo estudada principalmente para ruminantes como bovinos de corte (Mendonça et al, 2015), bovinos de leite (Oliveira et al, 2016) e ovinos (Goes et al, 2010;Dorigon e Gai (2016), entretanto, são escassos os estudos para os não ruminantes, havendo alguns trabalhos com juvenis de jundiá (Lovatto et al, 2014;Pettro et al, 2014), tilápias do Nilo (Moura et al, 2015) e frangos de corte (Ledoux et al, 1999). Portanto, objetivou-se com o presente trabalho determinar o desempenho de frangos de corte na fase inicial de vida, alimentados com farelo de crambe como fonte proteica para a ração.…”
Section: Resultsunclassified
“…New technologies for glucosinolate detoxification, such as chemical and physical treatments, reducing the amount to 450 mg kg −1 DM on crambe meal, could allow the full substitution of soybean meal in ruminant diets [98]. Recent studies reported that crambe meal can be valuably included in fish diets (i.e., silver catfish, Rhamdia quelen) as sustainable replacement of fish meal [27,28].…”
Section: Crambe Meal Usesmentioning
confidence: 99%
“…On the other hand, untreated CM can be used in broiler chicken diets at low levels (50-100 g kg −1 ) without or with minimal adverse effects on weight gain and health (Ledoux et al 1999). Additionally, no differences in growth or biochemical parameters were observed in jundiá, Rhamdia quelen, fed diets containing 208.4 g kg −1 of untreated CM, compared with a control diet (0% CM) (Pretto et al 2014).…”
Section: Introductionmentioning
confidence: 98%
“…Its byproducts (crambe meal/cake) are arousing interest from companies, research institutions and universities as an alternative feedstuff in animal production (Pitol et al 2010). Defatted crambe meal/cake originating from the dehulled seeds has potential as alternative feedstuff for ruminants (Araújo et al 2018; Moura et al 2017) and non-ruminant animals (Barbosa et al 2017;Pretto et al 2014;Vieira et al 2020) due to its high protein content (280-460 g kg −1 CP) and well-balanced amino acid pro le (Baker et al 1977;Carlson and Tookey 1983).…”
Section: Introductionmentioning
confidence: 99%